PROSPECTS OF TURKMENISTAN'S FOREIGN POLICY AND UZBEKISTAN'S NATIONAL INTERESTS - Sheraliev Nurali Sherali ugli (Modern American Journals, 2025)
The essence of this article is that the renewed relations with the political will of the presidents of these two neighboring countries, located in the Central Asian region, have been one of the main factors in the rapid development of all areas. However, these seen the raising of cooperation all spheres between two states. Also, this article also provides a detailed analysis of the relations between these two bordering countries in all areas.
Keywords: Multilateral diplomacy, geopolitical, tendency, border, territory, neighbor countries, international relations, initiative, cooperation.